PEMASARAN KEWIRAUSAHAAN DAN KINERJA USAHA MIKRO KECIL DAN MENENGAH - Andharini, Sri Nastiti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2012)
Small industry has a considerable role in the manufacturing sector in terms of the number of business units, the absorptive capacity of the workforce and supporting household income ladder. Distrust of the ability of micro, small and medium enterprises (UMKM) in the era of globalization, free-market-oriented mechanism is quite reasonable, because of the limitations that exist within the group. UMKM performance can be improved and developed, the UMKM have to do some things, namely to develop marketing objectives, develop the marketing area, the sale price appropriate packaging, developing marketing channels, maintain the typical product, develop a range of products and packaging, pay attention to the wants and needs of consumers